Stopping criteria for channel estimation for turbo decoding over flat fading channel - Srivastava Richa. (2008)
In this dissertation, we first study the encoding and decoding of turbo codes followed by the iterative channel estimation for turbo codes in flat fading channel and finally we investigate various stopping criteria for iterative channel estimation for turbo decoding. Secondly, we incorporate a Hard-Decision-Aided (HDA) stopping criterion for the turbo decoding in which no stopping criterion for channel estimation process is considered.